Pengaruh Tingkat Kecerahan Layar Smartphone terhadap Daya Tahan Baterai - Adelyna Oktavia Nasution; Amanda Putri Rizkita; Raisya Aulia; Al Hafiz Okliano Hardianta; Rizkan El Fattah (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines user awareness of the influence of smartphone screen brightness on battery power consumption. Of the 80 respondents, 100% answered